Betulin Alleviates the Inflammatory Response in Mouse Chondrocytes and Ameliorates Osteoarthritis via AKT/Nrf2/HO-1/NF-κB Axis - Ren, Chenghao; Jin, Jie; Hu, Wei; Chen, Qi; Yang, Jian; Wu, Yaosen; Zhou, Yifei; Sun, Liaojun; Gao, Weiyang; Zhang, Xiaolei; Tian, Naifeng (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a common degenerative joint disease featuring the degeneration, destruction and ossification of cartilage. Inflammation which may facilitate OA occurrence and development is considered as the main pathological factor. Betulin, a natural product extracted from birch bark, has been commonly used for inflammation treatment; however, its role in OA remains unclear. This study is aimed to explore whether betulin can suppress IL-1β induced inflammation in chondrocytes and alleviate osteoarthritis in vitro and in vivo. In in vitro studies, the generation of pro-inflammatory factors, such as interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), prostaglandin E2 (PGE2) and nitric oxide (NO) was assessed using enzyme linked immunosorbent assay (ELISA) and the Griess Reaction. As revealed by results, betulin inhibited the expression of pro-inflammatory mediators. In addition, the protein expressions of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), matrix metalloproteinase (MMP-13), thrombospondin motifs 5 (ADAMTS5), Collagen Ⅱ and Aggrecan were quantified using western blot analysis. We found that betulin can inhibit the generation of COX-2 and iNOS induced by IL-1β, indicating that betulin has anti-inflammatory effects in chondrocytes. Furthermore, betulin down-regulates the expression of MMP-13 and ADAMTS-5 and up-regulates the expression of Collagen Ⅱ and Aggrecan, indicating that it can inhibit the degradation of extracellular matrix. In mechanism, betulin activated AKT/Nrf2 pathway and inhibits the phosphorylation of p65. In in vivo studies, that administration of betulin in vivo can inhibit cartilage destruction and inflammatory progression. Therefore, these findings suggest that betulin may alleviate IL-1β induced osteoarthritis via AKT/Nrf2/HO-1/NF-κB signal axis, and betulin may be a potential drug for the treatment of OA.